Comparison of inbred mouse strains shows diverse phenotypic outcomes of intervertebral disc aging. Issue 5 (22nd April 2020) - Novais, Emanuel J.; Tran, Victoria A.; Miao, Jingya; Slaver, Katie; Sinensky, Andrew; Dyment, Nathaniel A.; Addya, Sankar; Szeri, Flora; van de Wetering, Koen; Shapiro, Irving M.; Risbud, Makarand V.
Abstract: Intervertebral disc degeneration presents a wide spectrum of clinically degenerative disc phenotypes; however, the contribution of genetic background to the degenerative outcomes has not been established. We characterized the spinal phenotype of 3 mouse strains with varying cartilage‐regenerative potential at 6 and 23 months: C57BL/6, LG/J and SM/J. All strains showed different aging phenotypes. Importantly, LG/J mice showed an increased prevalence of dystrophic disc calcification in caudal discs with aging. Quantitative‐histological analyses of LG/J and SM/J caudal discs evidenced accelerated degeneration compared to BL6, with cellular disorganization and cell loss together with fibrosis of the NP, respectively. Along with the higher grades of disc degeneration, SM/J, at 6M, also differed the most in terms of NP gene expression compared to other strains. Moreover, although we found common DEGs between BL6 and LG/J aging, most of them were divergent between the strains. Noteworthy, the common DEGs altered in both LG/J and BL6 aging were associated with inflammatory processes, response to stress, cell differentiation, cell metabolism and cell division. Results suggested that disc calcification in LG/J resulted from a dystrophic calcification process likely aggravated by cell death, matrix remodelling, changes in calcium/phosphate homeostasis and cell transformation. Lastly, we report 7 distinct phenotypes of human disc degeneration based on transcriptomic profiles, that presented similar pathways and DEGs found in aging mouse strains. Together, our results suggest that disc aging and degeneration depends on the genetic background and involves changes in various molecular pathways, which might help to explain the diverse phenotypes seen during disc disease. Abstract : This study investigates how genetic background influences the acquisition of specific morphological phenotypes in the intervertebral disc with aging. By uncovering the aging transcriptomic signature of three inbred mouse strains, and distinct transcriptomic profiles in human degenerated discs, our studies shed light on the wide spectrum of phenotypes presented during disc disease.